Photocatalytic Performance Study of Organophosphorus-Doped Tungsten Trioxide and Composite Materials - Ping Zhang; Jiayu Sun; null Qi wang; Wei Chen; Xiaochen Li (International Journal of Chemical Engineering)
The present study successfully produced a highly effective and stable organ phosphorus-doped tungsten trioxide (P-WO3) photocatalyst by a combination of hydrothermal and postcalcination methods. The crystallites, morphologies, and optical properties of the produced WO3 and P-WO3 crystals were investigated. The results indicated that P was consistently doped into the WO3 lattice in a pentavalent-oxidation state (P5+). Additionally, charge carrier traps capable of accepting photoelectrons were created. Additionally, the optical band gap was reduced from 2.4 to 2.33 eV. The degradation of methyl blue by photocatalysts was utilized to evaluate the photocatalytic performance of the synthesized P-WO3 samples at varied P concentrations (MB). The sample containing 6% -P-WO3 exhibited the best photocatalytic performance, degrading 96 percent of MB in 120 minutes, which was more than four times faster than the pure WO3 sample. The practicality of the synthesized P-WO3 was determined using samples from two residential wastewater treatment plants. When treating real wastewater with low organic matter concentrations, the P-WO3 demonstrated strong photodegradation performance. The creation of hydroxyl radicals (OH) and photography-created holes (h+) could be the key protagonists of photocatalytic activity in the P-WO3.